A fluorescent pH probe for evaluating the freshness of chicken breast meat. (1st August 2022) - Liu, Yuning; Yu, Yanan; Meng, Qingshi; Wei, Qing; He, Weizhao; Zhao, Qingyu; Tang, Chaohua; Feng, Xiaohui; Zhang, Junmin
Highlight: A new pH fluorescent probe Nap-MOR was synthesized; Nap-MOR was used for evaluating the freshness of chicken breast meat; The detection range of Nap-MOR covers normal fresh, defective and spoiled meat. Abstract: A fluorescent probe, Nap-MOR, based on the naphthalimide fluorophore, was designed and developed for pH measurement in aqueous solutions. Nap-MOR had a close linear relationship between fluorescence intensity and pH, in the range 4.5–8, which covers the full range of pH found in normal fresh, defective and spoiled meat. pH measurement with Nap-MOR was free from interference by a wide range of ions and biochemicals found in meat and the results were not significantly different in comparison with a pH meter. Therefore, Nap-MOR is a robust and convenient way to evaluate the freshness of chicken breast meat by measuring its pH.